Kompetensi Keahlian di SMKN 6 Pertanian Jeneponto Sulawesi Selatan - Siswantari -- (Jurnal Pendidikan dan Kebudayaan, 2012)
The aims of this study is to investigate the gap between industrial needs and the competences earned at vocational school of agricultural that has been conducted at SMK 6 Jeneponto, South Sulawesi. The study was motivated by the fact that the SMK 6 alumni are suffered from unemployed. The investigation has been performed through interview with stakeholders and focused on how the competency development conducted at the school could fulfill the local industry needs. It has been found that the school lacks of competences which are required by the local partners.